Critical perspectives on the (re)development of Westdene, Bloemfontein - Hoogendoorn, Gijsbertus (University of the Free State, 2006)
The study focuses on the development of Westdene, Bloemfontein. Westdene is one of Bloemfontein’s oldest neighbourhoods and has undergone a range of changes since its establishment in 1903. Following a review of the development of Westdene over the past century, this investigation provides a critical reflection on the urban changes that have taken place in this neighbourhood, including the decentralisation of office and retail functions, the development of entertainment amenities, gentrification in parts of the neighbourhood, crime and fear of crime in the former CBD and the neighbourhood itself. Drawing on the findings of the investigation the study attempts to make a contribution towards our understanding of neighbourhood changes in post-apartheid cities. Moreover, the investigation challenges the commonly held notion that urban compaction and diversification of land-uses lead to integrated and efficient neighbourhoods, or city districts. On the contrary, the result of this study contradicts this perception, demonstrating that despite the multiple uses of Westdene as a location of employment, recreation and residence, it has developed into a highly fragmented urban space.

Die studie fokus op die ontwikkeling van Westdene, een van die oudste woonbuurte in Bloemfontein. Sedert die ontstaan van hierdie woonbuurt in 1903, het dit talle veranderinge ondergaan. Nadat die ontwikkeling van Westdene oor die laaste eeu geskets is, word die stedelike veranderinge wat in hierdie woonbuurt plaasgevind het krities bespreek. Die desentralisasie van kantoor- en verkoopsfunksies, die ontwikkeling van vermaaklikheidsgeleenthede, gentrifikasie in sekere areas van die woonbuurt, misdaad en gepaardgaande die vrees vir misdaad in genoemde woonbuurt sowel as die sentrale sakekern, word onder andere behandel. Die studie dra by tot die kennis van woonbuurtverandering in die post-apartheid era. Verder daag die studie ook die algemene persepsie uit dat stedelike verdigting en diversifikasie van grondebruik lei tot geïntegreerde en volhoubare woonbuurtes of stedelike areas. Inteendeel, die bevindinge van die studie weerspreek hierdie siening, deur uit te wys dat Westdene, as gevolg van die verskeidenheid van grondgebruike, naamlik die van werk, rekreasie en verblyf, in ŉ uiters gefragmentterde stedelike ruimte ontwikkel het. 139
Dissertation (M.A. (Geography))--University of the Free State, 2006
Keywords: Urban renewal -- South Africa -- Bloemfontein -- Westdene; City planning -- South Africa -- Bloemfontein -- Westdene.; Entertainment; Crime; Gentrification; Fragmentation; Postmodernism; Renewal; Compaction; Neighbourhood; Decentralisation